State policy and juvenile crime in South Africa, 1911-1939 - Chisholm, Linda (PINS-Psychology in Society, 2026)
Recent writing by psychologists and social workers is curiously ahistorical. That historical analysis which does exist, apart from the work by Louw (1), replicates on the whole versions of history and theoretical approaches which do not contribute to uncovering for psychologists and social workers the historical roots of their practices. These shape the terrain on which psychologists and social workers operate to this very day. It is important that psychologists and social workers understand their own history theoretically if new ways of transforming the field in South Africa are to be developed. This article will try to cast light on one aspect of the history of state policy and social welfare in South Africa. It argues that racially differential means for dealing with black and white juvenile delinquents were developed in the twenties and thirties through the development of institutional and non-institutional approaches. These represented the differentially repressive and ideological means by which social relations in South Africa were regulated: for blacks largely through the prisons, repatriation to the rural areas and apprenticeships to white farmers, for Europeans largely through the family and education. Both signified direct intervention by the state in labour control and discipline on the one hand, and labour reproduction on the other. In the case of Europeans, the shift in the 1920s to the use of probation, maintenance grants known as "mother's pensions" and industrial schools formed part of the wider state strategy to intervene in the "poor white" and working class family. As much as these were concessions to the white working class, and rights won by women, their development also saw the expansion of agencies involved in direct regulation and state surveillance of civil society (2). In the case of blacks, the absence of welfare facilities and the reliance on coercive techniques and procedures such as imprisonment, apprenticeship and repatriation to the rural areas was directly tied to the state's amenability in meeting the labour needs of agrarian and mining capital.